Behaviour and heart rate response in children and adolescents undergoing anesthesia with considerably altered (Covid-19-Related) safety precautions. - J. Chin; L. Barneto; M. Ellington; A. Hutton; M. Johnson; A. M. Hogan (Pediatric Anesthesia and Critical Care Journal, 2021)
Introduction The COVID-19 pandemic imposed on us the requirement for fast and significant change to our anesthetic practice. Some anesthetic safety precautions (e.g. full personal protective equipment and restricting parent-attendance at anesthesia induction) had the potential to alter behavioral and physiological (anxiety-related) responses in children and adolescents undergoing surgery during this time, de- spite increased use of oral pre-sedation. We explored our unique dataset in order to provide preliminary and oppor- tunistic data addressing this issue. Methods 93 children and adolescents (1-16 years) underwent an- esthesia for surgery at our large tertiary hospital during the first U.K. peak of the COVID-19 pandemic (approx- imately April 2020). All anesthetics were performed with COVID-19 safety precautions. A control group consisted of 91 children and adolescents undergoing anesthesia for surgery immediately before the peak-pandemic. Behavior was assessed by anesthetist-rating of cooperation and calmness of children and adolescents at anesthesia induc- tion, and subsequently by recovery nurse subjective rat- ing. Multiple heart rate values obtained for each child/ adolescent pre- and post-procedure were age-normalised and explored for incidence of tachycardia, which can re- late to anxiety. Results Accounting for age group, behavior and heart rate values were comparable across groups. This was despite signif- icant changes to anesthetic practice including reduced use of inhalational induction and therefore increased awake intravenous cannulation. Conclusion Behavior and heart rate data indicate some stability in children's and adolescent's acute response to anesthesia in the context of otherwise significant change to our prac- tice. However, efforts should still be directed at assessing possible late-emerging behavioral and emotional re- sponses to this altered-anesthesia experience, as this may yet influence how this cohort of children and adolescents engages with any future healthcare procedures.